Blockchain technology for agriculture traceability systems in South Africa - Brummer, Ulrich (Graduate School of Business (GSB), 2025)
This research explores the integration of blockchain technology in South Africa's agricultural sector to enhance food traceability. The study critically examines the evolving landscape of agri-food markets, transitioning from traditional to modern supply chains marked by globalisation and increased emphasis on quality and safety. The role of blockchain technology in addressing traceability challenges is assessed through an extensive literature review, featuring diverse perspectives and insights. The study investigates the application of blockchain in food traceability through an analysis of various models and frameworks presented in contemporary research studies. Notably, the research highlights the significance of traceability in ensuring food safety, quality, and sustainability, emphasising the growing consumer demand for transparent information about the origin and journey of food products. Past global food scandals have highlighted the need for robust traceability systems and highlighted the urgency of quick crisis identification and resolution. Blockchain technology emerges as a transformative solution for food traceability, offering immutability, transparency, and decentralised control. The study acknowledges the challenges associated with blockchain adoption, including issues related to data governance, interoperability, regulatory frameworks, implementation costs, and the need for stakeholder education. The research underscores the importance of sector-wide consensus and standardisation efforts to overcome these challenges and facilitate the transition from blockchain pilots to enduring implementations. The research is concluded by highlighting the implications of blockchain adoption, including enhanced transparency, improved food safety, and increased consumer confidence. It emphasises the need for collaborative efforts between government and industry stakeholders to establish supportive regulations and standardised protocols. The study identifies research gaps, including the exploration of advanced consensus mechanisms, privacy-preserving techniques, and the integration of artificial intelligence for data analytics. Continuous research and collaboration are proposed to address these gaps and drive ongoing innovation in the field. The study provides a comprehensive overview of the current state of blockchain technology in South African agriculture, offering insights for practitioners, policymakers, and researchers to navigate the dynamic intersection of technology and food traceability.